Paternalisme industriel – jedna z odpovedí na sociálnu otázku - Jakub Štofaník (Historicka Sociologie, 2020)
The article pays attention to industrial paternalism as one of the models of employer-labour relations that have emerged during the 19th century. It focuses in particular on the French environment, in which industrial paternalism strongly resonated and where we can find many of its important actors. The study brings on the light its precursors and inspirations in the concept of patronage of Frédéric Le Play as well as the interactions between state, entrepreneurship, and working class. The text introduces main characteristics of this managerial approach in the historical context of the end of the 19th and first half of the 20th century with the changing nature of French industry and massive immigration of labour force. It analyses historiographic production devoted to this phenomenon and offers various ways of its interpretation.